Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1107/s139900471500704x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a novel subfamily of leucine-rich repeat proteins from the human pathogen Leptospira interrogans

Abstract: Pathogenic Leptospira spp. are the agents of leptospirosis, an emerging zoonotic disease. Analyses of Leptospira genomes have shown that the pathogenic leptospires (but not the saprophytes) possess a large number of genes encoding proteins containing leucine-rich repeat (LRR) domains. In other pathogenic bacteria, proteins with LRR domains have been shown to be involved in mediating host-cell attachment and invasion, but their functions remain unknown in Leptospira. To gain insight into the potential function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…Bioinformatic analyses of LRR protein sequences predicted extracellular localization for the majority of these proteins (Miras et al, ), and some of these predictions have been confirmed experimentally in a previous study quantifying Leptospira exoproteins (Eshghi et al, ). In that study, LIC10831 was characterized as enriched in the culture medium, suggesting active export.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Bioinformatic analyses of LRR protein sequences predicted extracellular localization for the majority of these proteins (Miras et al, ), and some of these predictions have been confirmed experimentally in a previous study quantifying Leptospira exoproteins (Eshghi et al, ). In that study, LIC10831 was characterized as enriched in the culture medium, suggesting active export.…”
Section: Resultsmentioning
confidence: 71%
“…Our previous study on the structure of several leptospiral LRR proteins suggested a similarity in structure and binding pocket of LIC10831 to InlA from L. monocytogenes (Miras et al, ), a well‐studied human epithelial cadherin (hE‐Cad)‐binding protein (Bierne et al, ; Wollert, Heinz, & Schubert, ). Due to this similarity, we decided to investigate whether LIC10831 is also capable of interacting with this host protein.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Crystals of the leucine-rich repeat (LRR) protein from L. interrogans containing residues 30-377 were kindly provided by Ahmed Haouz (Institut Pasteur) and William Shepard (Synchrotron SOLEIL). Details of the crystal preparation have been published elsewhere (Miras et al, 2015).…”
Section: Examplesmentioning
confidence: 99%
“…Earlier investigations (Evangelista and Coburn, 2010;Chaemchuen et al, 2011;Domingos et al, 2012) and more recent studies Gomard et al, 2016;Vieira and Nascimento, 2016) have described antigens that mediate host-pathogen interactions among Leptospira species. Recent genome analyses studies indicated that the leptospira characterized as pathogenic possess a number of genes that coded for proteins containing leucine-rich repeat (LRR) domains (Nitipan et al, 2013;Miras et al, 2015), presumed to be important in structural motifs of different host proteins (Miras et al, 2015). Interestingly, these characteristics were not observed in saprophytes.…”
Section: Determinant Of Leptospira Pathogenesismentioning
confidence: 99%